THE INFLUENCE OF LIVE STREAMING FEATURES ON MEDIATED PURCHASE INTENTION TRUST IN E-COMMERCE SHOPEE - Nadia Shalaty; Ikramuddin; Rusydi; Muchsin (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
Indonesia's e-commerce sector is predicted to continue to increase until 2027, but some Indonesians are not yet actively using e-commerce and are starting to reduce spending on e-commerce Shopee and then switch to social commerce such as TikTok and Instagram. This research focuses on Shopee e-commerce users who have watched Shopee live streaming. The aim of this research is to test the live streaming feature and its influence on purchase intention on Shopee e-commerce at the Faculty of Economics and Business, Malikussaleh University. This research also tests trust as a mediator to increase purchase intention on Shopee e-commerce. This research is a quantitative research using a purposive sampling technique with a sample of 140 students from the Faculty of Economics and Business, Malikussaleh University. The data source comes from primary data obtained through distributing questionnaires. The data analysis technique used is PLS-SEM with SmartPLS software. The research construct is a second order multidimensional construct with The Embedded Two-Stage Approach. The research results show that the live streaming feature has a positive and significant effect on trust and purchase intention. Then trust has a positive and significant effect on purchase intention, and there is a strong mediating influence between the relationship between the live streaming feature and purchase intention through trust. This research concludes that the trust built in live streaming is a key factor in driving purchase intention. These findings provide practical implications for e-commerce managers and sellers in using live streaming features to increase trust and encourage purchases.